The relationship between bank concentration and interest rates - Tijana Kaličanin; Zoran Grubišić; Sandra Kamenković (Journal of Central Banking Theory and Practice, 2023)
The aim of this paper was to analyse the relationship be-tween market concentration and market interest rate. Taking intothought the relationship between the level of concentration within amarket and the level of competition, it can be deduced that an incre-ment in concentration results in a decrease in competition. In orderto test the above mentioned relationship, the authors used a paneldataset covering the period 2010Q1-2019Q4. The set includes quar-terly data of all banks that operated in the Republic of Serbia. Firstof all, a correlation analysis was applied to determine whether thereis a quantitative agreement between interest rates and concentrationmeasures, and also a regression analysis i.e., econometric evaluationof panel regression models. In order to test the hypothesis, a totalof 12 regression equations were applied. Results indicate that thatthe concentration indicators have a statistically significant and nega-tive impact on the overall active interest rate in only two regressionmodels, which is inadequate to support the hypothesis that there ex-ists a systematic influence of concentration in the banking industryon interest rates. As a conclusion, the regression analysis imposesthat the variations of the total loan interest rate can be explainedto the greatest extent by the systematic and robust influences of thekey policy rate of the NBS and the interannual inflation rate for thegiven quarter, as well as by the robust tendency of a linear declineover time.
Keywords: G21; E58; L10; 330; market concentration; loan; interest rate